Application of Local Wisdom of Wayang Figures: Building Student Character Education in Elementary Schools (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the Study: This research aims to describe and analyze the methods of building student character by implementing local wisdom of wayang characters at Elementary School Segulung 05. It examines this process's inhibiting and supporting factors and evaluates its overall impact. Methodology: The research adopts a case study design with a qualitative approach. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted using Milles & Huberman’s method, which encompasses data reduction, data presentation, and conclusions. Main Findings: The study reveals that character formation in students is effectively facilitated through the integration of wayang figures' local wisdom. This is achieved via strategies such as introducing wayang characters and their traits, using exemplars, narrating stories or giving advice, and incorporating wayang-related materials into Javanese language lessons. Supporting factors for this character-building process include the unique and engaging form of wayang, students' enthusiasm for listening to stories, and the broad acceptance of wayang across different societal groups. Novelty/Originality of the Study: The novelty of this research lies in its detailed exploration of character education through the cultural medium of Wayang, showcasing innovative ways to leverage local wisdom in modern education. By integrating Wayang characters and their moral lessons into the curriculum, the study provides a unique approach to character building. This method enhances student engagement and cultural appreciation and fosters moral development through culturally resonant narratives and practical examples.